Spiegare e argomentare
y = SIN(x)
y = COS(2·x) = COS(x)^2 - SIN(x)^2
SIN(x) = Υ
COS(x) = Χ
risolvo:
{Υ = Χ^2 - Υ^2
{Υ^2 + Χ^2 = 1
risolvo: [Υ = -1 ∧ Χ = 0, Υ = 1/2 ∧ Χ = √3/2, Υ = 1/2 ∧ Χ = - √3/2]
{SIN(x) = 1/2
{COS(x) = √3/2
risolvo: [x = pi/6]
altro estremo:
pi - pi/6 = 5·pi/6
SIN(x) - (COS(x)^2 - SIN(x)^2) = - 2·COS(x)^2 + SIN(x) + 1
∫(- 2·COS(x)^2 + SIN(x) + 1)dx =
= - COS(x)·(SIN(x) + 1)
- COS(5/6·pi)·(SIN(5/6·pi) + 1) = 3·√3/4
- COS(pi/6)·(SIN(pi/6) + 1)= - 3·√3/4
A = 3·√3/4 - (- 3·√3/4)= 3·√3/2